Reporte de caso: trombosis venosa cerebral en un paciente con virus de inmunodeficiencia humana - Valentina Ferrer-Valencia (Asociación Colombiana de Infectología, 2021)
Cerebral venous thrombosis (CVT) is a rare clinical presentation of venous thromboembolism characterized by headache, seizures, neurological deficits and papi-lledema. The diagnosis is confirmed using computed tomography scan (CT scan) and magnetic resonance imaging (MRI) of the brain. CVT has an important relationship with the human immunodeficiency virus (HIV) given that HIV-positive patients may present with blood hyperviscosity, irregular levels of endogenous anticoagulation factors and risk of sepsis among others, that predispose to prothrombotic states and vascular injury such as CVT. The treatment of CVT is anticoagulant therapy, generally unfractionated heparin or low molecular weight heparin for the early phase and oral anticoagulants such as warfarin for the late phase. This case reports the first documented case of CVT in an HIV positive patient in Colombia.